Pengaplikasian pendekatan konstruktivisme dalam pengajaran dan pembelajaran Bahasa Melayu - Mahmud, Hasnita (2011)

(untitled)
This study focuses on constructivism concept of teaching and learning process. This study is inclusive of the background study, research problems that refer to the matters that will be conducted in this research, methodology and definitions of the concepts that are central to this study. This study was carried out to identify the status of the implementation of the constructivism concept of teaching and learning process in Bahasa Melayu in 1 (one) school at Gua Musang, Kelantan. This study focuses on 5 (five) aspects according to Needham’s 5-Phase Constructivism Model. The phases are orientation, idea initiation, idea restructure, idea usage, and reflection.The literature review about constructivism concept of teaching and learning was explained in detailed. The quantitative methodology was used in this study and 150 students were selected as respondents for this study. A set of questionnaires that contained two parts was used as the instrument to conduct this study. The first part is regarding the respondent’s personal background while the second part consists of 25 items for assessing the implementation of the above phases. The data collected was analyzed using Statistical Package for Social Science (SPSS) version 17.0 and the data obtained is based on the frequency, percentage and mean. The result of this study shows that the concept of Constructivisme in learning and teaching Bahasa Melayu had been practiced. However, the idea restructure phase was identified at the lowest rate. Based on the findings, some suggestions were made to ensure that the objective of teaching and learning Bahasa Melayu is fully implemented.